Effect of Depolymerized Holothurian Glycosaminoglycan (DHG) on Tissue Factor Pathway Inhibitor: In Vitro and In Vivo Studies - Nagase, Hideki; Enjyoji, Kei-ichi; Kamikubo, Yu-ichi; Kitazato, Keiko T; Kitazato, Kenji; Saito, Hidehiko; Kato, Hisao (Thrombosis and Haemostasis, 1997)
Depolymerized holothurian glycosaminoglycan (DHG) is a glycosaminoglycan extracted from the sea cucumber Stichopus japonicusSelenka. In previous studies, we demonstrated that DHG has antithrombotic and anticoagulant activities that are distinguishable from those of heparin and dermatan sulfate. In the present study, we examined the effect of DHG on the tissue factor pathway inhibitor (TFPI), which inhibits the initial reaction of the tissue factor (TF)-mediated coagulation pathway. We first examined the effect of DHG on factor Xa inhibition by TFPI and the inhibition of TF-factor Vila by TFPI-factor Xa in in vitro experiments using human purified proteins. DHG increased the rate of factor Xa inhibition by TFPI, which was abolished either with a synthetic C-terminal peptide or with a synthetic K3 domain peptide of TFPI. In contrast, DHG reduced the rate of TF-factor Vila inhibition by TFPI-factor Xa. Therefore, the effect of DHG on in vitroactivity of TFPI appears to be contradictory. We then examined the effect of DHG on TFPI in cynomolgus monkeys and compared it with that of unfractionated heparin. DHG induced an increase in the circulating level of free-form TFPI in plasma about 20-fold when administered i.v. at 1 mg/kg. The prothrombin time (PT) in monkey plasma after DHG administration was longer than that estimated from the plasma concentrations of DHG. Therefore, free-form TFPI released by DHG seems to play an additive role in the anticoagulant mechanisms of DHG through the extrinsic pathway in vivo. From the results shown in the present work and in previous studies, we conclude that DHG shows anticoagulant activity at various stages of coagulation reactions, i.e., by inhibiting the initial reaction of the extrinsic pathway, by inhibiting the intrinsic Xase, and by inhibiting thrombin.